Preoperative NLR and PLR in the middle or lower ESCC patients with radical operation. (7th March 2016) - He, Y.‐F.; Luo, H.‐Q.; Wang, W.; Chen, J.; Yao, Y.‐W.; Yan, Y.; Wu, S.‐S.; Hu, X.‐X.; Ke, L.‐H.; Niu, J.‐Y.; Li, H.‐M.; Ji, C.‐S.; et al.
Abstract : Neutrophil lymphocyte ratio (NLR) and platelet lymphocyte ratio (PLR) had been analysed in many kind of tumours, but its role of predict the oesophageal squamous cell carcinoma (ESCC) patients' prognosis was not reach a consensus. Relationship between NLR, PLR and ESCC located in the middle or lower segment was evaluated. 317 patients with ESCC who underwent attempted curative oesophagectomy were analysed in this study. 157 and 98 patients had elevated NLR and PLR respectively (NLR >3.3 and PLR >150). The median overall survival time (OS) and disease‐free survival (DFS) was 34.1 and 19.2 months respectively. Multivariate analysis found PLR >150 ( P = 0.018, HR 1.426, 95%CI 1.063–1.912) accompanied by male, lymphatic metastases, tumour size more than 3 cm, tumour located at middle segment and poor differentiation were associated with significantly worse DFS. Meanwhile, gender, lymphatic metastases, tumour location and differentiation along with PLR >150 ( P = 0.003, HR 1.595, 95% CI 1.172–2.170) and NLR>3.3 ( P = 0.039, HR 1.367, 95% CI 1.015–1.840) were all independent prognostic factors for OS. Preoperative NLR and PLR might be used as predictive factors in patients with ESCC. For DFS, elevated PLR compared to NLR may have an advantage to indicate poor prognosis.